Phylogeography and genetic population structure of Caribbean sharpnose shark Rhizoprionodon porosus - Mendonca, Fernando F. [UNESP]; Oliveira, Claudio [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Foresti, Fausto [UNESP] (Springer, 2011)
Sharks of the genus Rhizoprionodon are among the most important predators along the coastal marine ecosystems, and they represent an important economic resource for the small-scale fisheries. To properly manage and conserve exploited shark species, detailed analyses of their population structure are needed. To evaluate the gene flow and levels of the genetic diversity among populations of the Caribbean sharpnose shark R. porosus, we identified the nucleotide sequence based on collections (n = 321 specimens) from 10 different areas, including the Caribbean Sea and several locations along the entire Brazilian coast. The analysis of 802 nucleotides from the mitochondrial DNA control region revealed 53 distinct haplotypes. The majority of these haplotypes were restricted to their collection locales with a significant genetic structure detected among the overall populations (Phi(ST) = 0.237, P < 0.0001). The data suggest a population division with two distinct management units in the western Atlantic. These management units are likely separated by the Equatorial Current. The strong population structure in R. porosus indicates that regional populations, if depleted, will not recover swiftly through immigration.
Keywords: Conservation genetics; Biogeography; Fishery management; Coastal sharks; Population structure; Rhizoprionodon porosus